2011
DOI: 10.4028/www.scientific.net/amr.201-203.2814
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrothermal Depolymerization Technology and Kinetics of DGEBA/EDA Epoxy Resin

Abstract: Depolymerization of thermosetting epoxy resin with environmental-friendly heteropolyacid catalyst at temperatures between 270°C-350°C in H2O medium. The effect of the factors catalyst, temperature and time on the depolymerization was researched. UV spectrum was used to characterize the thermal stability of heteropolyacid catalyst. The products of depolymerization were analysed qualitatively and quantitatively by means of GC/MS and GC. The results indicated that the main depolymerized products were phenol, p-is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Several technologies have emerged for the elimination or recycling of epoxy‐based systems. For example, Zhang et al suggested the catalytic hydrothermal depolymerization of an amine‐cured epoxy resin, Dang et al dealt with chemical treatment in nitric acid solutions of epoxy‐amine systems and Lucignano et al studied recycling as foams of epoxy‐polyester resin. Among these methods, one concerns the crosslinking/decrosslinking of polymers using dynamic reactions such as the Diels–Alder (DA) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies have emerged for the elimination or recycling of epoxy‐based systems. For example, Zhang et al suggested the catalytic hydrothermal depolymerization of an amine‐cured epoxy resin, Dang et al dealt with chemical treatment in nitric acid solutions of epoxy‐amine systems and Lucignano et al studied recycling as foams of epoxy‐polyester resin. Among these methods, one concerns the crosslinking/decrosslinking of polymers using dynamic reactions such as the Diels–Alder (DA) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The high efficiency of acid catalysis was attributed to the strong coordination effect of acid with the C−N bonds. Therefore, different degradation systems such as phosphotungstic acid/H 2 O, 21 AlCl 3 /CH 3 COOH, 22 and ZnCl 2 /ethanol 23 have been developed, but the high temperature of 180−200 °C is still required for the complete degradation of the resin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9−12 Catalysts have been used to depolymerize epoxy resins at extreme temperatures and pressures, but not with complete depolymerization of the epoxy resin. 13 These processes are damaging, complicated, and expensive. Also, these extreme conditions for removal of epoxies limit the lifetime of devices held together by epoxy adhesives or covered by epoxy protective layers because the removal process is injurious to sensitive components of the devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For this reason, aggressive methods have been employed to recycle epoxies in the sense of removing them from the waste stream, but not in the sense of reprocessing the material for a new application while retaining the original mechanical properties at a minimal energy cost. Mechanical recycling (i.e., grinding) is capable of producing powders and fibers for fillers; otherwise, it typically requires extreme conditions such as heating to very high temperature to decompose the polymer (i.e., oxidizing above 400 °C) and/or using extremely aggressive solvents (e.g., concentrated nitric acid or warm sulfuric acid). Catalysts have been used to depolymerize epoxy resins at extreme temperatures and pressures, but not with complete depolymerization of the epoxy resin . These processes are damaging, complicated, and expensive.…”
Section: Introductionmentioning
confidence: 99%